Targeted transcriptional silencing of hepatitis B virus using designer epigenome modifiers expressed from in vitro transcribed mRNA - Singh, Prashika (University of the Witwatersrand, Johannesburg, 2025)
Approximately two-thirds of the world's population has been exposed to the hepatitis B virus (HBV), the causative agent of hepatitis B, with sub-Saharan Africa experiencing a high prevalence, where up to 8% of the population are chronic carriers. The persistence of HBV infection is largely due to the stable replicative intermediate, covalently closed circular DNA (cccDNA), which current treatments do not effectively target or eliminate. Consequently, a reliable cure for chronic hepatitis B (CHB) remains unavailable. Gene editing technologies, such as Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein (CRISPR/Cas), Transcription Activator-Like Effector Nucleases (TALENs), and Zinc Finger Nucleases (ZFNs), can directly target cccDNA and offer the potential to eliminate this reservoir. However, these methods are limited by the risk of off-target effects, including chromosomal deletions and translocations. In contrast, emerging epigenome editing technologies provide safer alternatives. Designer epigenome modifiers (DEMs) offer a less genotoxic option by modifying cccDNA epigenetically. DEMs, comprising DNA methyltransferase (DNMT) and Kruppel- associated box (KRAB) repressor domains along with a Transcription Activator-Like Effector- DNA binding domain (TALE-DBD) were designed to target the HBV surface (S), core (C), and polymerase (P) open reading frames (ORFs). Control DEMs lack a KRAB domain and contain catalytically inactive DNMT. Given the strategic positioning of CpG islands in the HBV genome, these regions make the viral genome an ideal target for DNA methylation. To improve the efficacy of already existing DEMs, this study evaluated the use of mRNA-based platforms (mRNA-based vectors, pmRNA-pA and pT7-(AG)) for expressing anti-HBV DEMs for the first time, allowing for targeted silencing of the S, C, and P ORFs of HBV in vitro. Sequences encoding the DEMs were cloned into an expression vector specifically designed for in vitro transcription of mRNA. In vitro transcribed anti-HBV DEM-encoding mRNA were transfected into liver-derived Huh7 and HEK 293T cells. Markers of viral replication, including HBV surface antigen (HBsAg) and viral surface and pregenomic RNA (pgRNA) and stimulation of interferon response genes were assessed. Bisulphite sequencing was used to confirm the methylation of HBV DNA, and 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays were conducted to assess the toxicity of the synthesized DEM RNA. The pT7- (AG) vector, featuring more stable regulatory sequences, a longer poly-A tract, and multiple termination codons, proved to be more effective than the original platform. DEMs expressed Abstract vi from this platform achieved a significant reduction in HBsAg levels, particularly with the complete substitution of uridine nucleotides with pseudouridine, incorporation of CleanCap® AG, and removal of dsRNA. HBsAg levels were reduced by 21-41 %, and up to 50-90 % reduction was observed with double transfection. Additionally, viral surface transcript levels decreased by 42-70 %, while pregenomic transcript levels decreased by 62-72 % correlating with increased trend in methylation at all three targeted CpG islands. There was no evidence of immune stimulation or metabolic toxicity, indicating that the observed transcriptional activity resulted from DEM activity and suggest that DEMs are safe. Furthermore, the SL and PL DEMs exhibited the greatest transcriptional silencing. This proof-of-concept study demonstrates that optimising mRNA stability, half-life, and immunogenicity can significantly enhance the efficacy of DEMs. However, further in vivo characterisation of these DEMs, along with an assessment of their duration of action at both on-target and off-target activities, is required. Nevertheless, targeted epigenome silencing of HBV through the use of epigenome editors expressed as in vitro transcribed mRNA represents a promising therapeutic approach for modulating viral replication and potentially treating CHB.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Hepatitis B virus,; vitro transcribed mRNA,; SDG-3: Good health and well-being